Language Portraits: Interpreting Linguistic and Cultural Identity among Heritage Langauage Learners - Ng, Boon Sim; Long, Qian; Abdul Halim, Hazlina; Wong, Ling Yann (Universiti Malaysia Pahang Al-Sultan Abdullah, 2024)
The chapter focuses on the relationship between language learning experiences, cultural identity, and adaptions of immigrant community descendants in preserving their language and culture.